An exploration of the feasibility, acceptability, and effectiveness of professional, multitasked community health workers in Tanzania. Issue 8 (3rd August 2017) - Baynes, Colin; Semu, Helen; Baraka, Jitihada; Mushi, Hildegalda; Ramsey, Kate; Kante, Almamy Malick; Phillips, James F.
ABSTRACT: Despite four decades of global experience with community-based primary health care, the strategic details of community health worker (CHW) recruitment, training, compensation, and deployment remain the subject of continuing discussion and debate. Responsibilities and levels of clinical expertise also vary greatly, as well as contrasting roles of public- versus private-sector organisations as organisers of CHW effort. This paper describes a programme of implementation research in Tanzania, known as the Connect Project, which aims to guide national policies with evidence on the impact and process of deploying of paid, professional CHWs. Connect is a randomised-controlled trial of community exposure to CHW integrated primary health-care services. A qualitative appraisal of reactions to CHW implementation of community stakeholders, frontline workers, supervisors, and local managers is reviewed. Results highlight the imperative to plan and implement CHW programmes as a component of a broader, integrated effort to strengthen the health system. Specifically, the introduction of a CHW programme in Tanzania should draw upon community structures and institutions and strengthen mechanisms to sustain their participation in primary health care. This should be coordinated with efforts to address poorly functioning logistics and supervisory systems and human resource and management challenges.